Fe, oxidative and nitrosative metabolism in the Antarctic limpet Nacella concinna - González, Paula Mariela; Puntarulo, Susana Ángela (Comparative Biochemistry and Physiology Part A: Molecular & Integrative Physiology)
The hypothesis of this work was that oxidative and nitrosative metabolism in the digestive gland (DG) of two limpet populations (intertidal and subtidal) of the Antarctic species Nacella concinna show different behavior when they were exposed to either intermittent (intertidal) or constant (subtidal) natural Fe. Total Fe content and labile Fe pool were higher in the DG of the subtidal compared to the intertidal population. However, no significant differences between populations were seen on the Fe atoms content of the isolated ferritin. Ascorbyl radical content was 2.0 ± 0.4 and 6.5 ± 0.8 pmol/mg FW in the DG of the intertidal and subtidal animals, respectively. Lipid damage, assessed as content of thiobarbituric reactive substances, was different between the tissues of intertidal and subtidal samples, 491 ± 102 and 1242 ± 367 pmol/mg FW, respectively. Catalase and superoxide dismutase activities showed no differences between the limpets. Nitric oxide (NO) content was 25 ± 3 and 22 ± 2 pmol/mg FW in DG from intertidal and subtidal animals, respectively. NO synthase-like (NOS-like) activity was evaluated supplementing the samples with the enzyme co-factors, and the inhibitory effect of Nω-nitro-L-arginine methyl ester hydrochloride was tested. NO generation rate was 3.4 ± 0.3 and 4.7 ± 0.6 pmol/min mg FW in DG from the intertidal and subtidal population, respectively. These results showed that the oxidative condition of the limpet population constantly covered by the Fe enriched water is more affected than the intertidal population. However, the nitrosative metabolism seems to be independent of the environmental high Fe content since similar NO steady state concentration and NOS-like activity were measured in both populations. Fil: González, Paula Mariela. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Houssay. Instituto de Bioquímica y Medicina Molecular. Universidad de Buenos Aires. Facultad de Farmacia y Bioquímica. Instituto de Bioquímica y Medicina ...